2022
DOI: 10.3390/ijerph192214901
|View full text |Cite
|
Sign up to set email alerts
|

Could Belief in Fake News Predict Vaccination Behavior in the Elderly?

Abstract: Willingness to get a vaccine was important during the COVID-19 pandemic. Previous studies suggest that vaccine hesitation during the pandemic could have been related to truth discernment, belief in information, exposure to misinformation, attitudes to vaccines, and conspiracy beliefs. Previous studies were mostly with younger adults, and studies with older adults are lacking. This study aimed to analyze the relationship between the trust or belief in fake online news (print news was not included), truth discer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Individuals aged 50 and over, as well as those between 30 and 49 years, demonstrated a greater inclination to believe in conspiracy theories compared to younger people. This finding could be explained by varying levels of exposure and attitudes toward vaccination, or it might suggest that aging is linked to decreased receptivity to information [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals aged 50 and over, as well as those between 30 and 49 years, demonstrated a greater inclination to believe in conspiracy theories compared to younger people. This finding could be explained by varying levels of exposure and attitudes toward vaccination, or it might suggest that aging is linked to decreased receptivity to information [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Sharing or belief in fake news has the potential to negatively impact health behaviors, as does belief in conspiracy theories. For instance, there is a negative association between belief in fake news containing vaccine‐related conspiracy theories and vaccination (Pakalniškienė et al., 2022). In this research, we found that a large portion (92/170) of the fake news spread during the crisis period (COVID‐19) included information about social identities, and that, in general, determining the accuracy of such news may be related to ingroup identification and perceived outgroup threat.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding COVID-19 vaccines, new conspiracy theories have surfaced, such as microchip injection, unchecked adverse effects, absence of safety assessment before vaccine distribution, and unproven vaccine effectiveness. Studies indicate that exposure to fake news diminishes the intention to receive the COVID-19 vaccine [ 24 ]. Even brief exposure to false information has been shown to potentially modify or influence human behavior [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even brief exposure to false information has been shown to potentially modify or influence human behavior [ 22 ]. As a result, conspiracy beliefs, trust in information, and brief exposure to online news can impact individuals’ vaccination choices [ 24 ]. Findings from a randomized controlled trial by Loomba et al [ 25 ] indicated that exposure to online disinformation about COVID-19 vaccines led to a significant decline in vaccination intent, in the samples from both the United States (6.4% points) and the United Kingdom (6.2% points).…”
Section: Introductionmentioning
confidence: 99%